Manejo de riego en el cultivo de papaya (Carica papaya) en el Ecuador - Jiménez Vera, Manuel Jolaow (2020)
Papaya cultivation is located in tropical and subtropical zones of Ecuador, with an estimated cultivated area of 2 942 hectares. With a greater surface in the provinces of Esmeraldas, Santo Domingo de los Tsáchilas, Los Ríos, Guayas, Santa Elena and, on a smaller surface, the provinces of Manabí, El Oro, Sucumbíos, Orellana and Pastaza. The papaya needs abundant water to produce good harvests, partly because the continuous production depends on the continuous growth of the stem and the formation of new leaves, since the product is born in their armpit. A lack of water that affects growth momentarily can cause flower drop and reduce yields by up to 50%. Although water requires dependence on various factors such as temperature, light, wind, soil and age of plants, several authors suggest correcting a quantity of 1,500 to 2,000 mm, well distributed throughout the year. A papaya plantation requires a constant supply of water, mainly in the first eight months of development. In this regard, various studies indicate that the greatest demand for water from this fruit tree occurs in the flowering and fruiting stages and that under high temperature conditions, the water requirement per plant is between 10 and 15 Lt daily. It is concluded that the gravity irrigation system is a system that can be used in this crop, provided that the slope is not very high. This gravity irrigation system is suitable for crops where there is a lack of resources. Furrow construction can be manual, which helps low-budget crops.